The Analysis of 3D Printing Thermoplastic Materials by Using FDM Technique - Shoukat Ali noonari; Amna Hafeez rajout; Hamza Shaikh Shaikh; Jabir Ali Ali; Aftab Ahmed Khuhro Khuhro; Faheem Ahmed Solangi Solangi (Sukkur IBA Journal of Emerging Technologies)
The size of the production run and the geometric complexity of the component are the primary factors limiting the use of standard manufacturing methods; thus, we are often compelled to employ procedures and equipment that raise the element's final cost. Since its rise to prominence as an additive manufacturing technique in the 2000s, 3D printing has been utilized extensively as a prototype technique. Through the gradual addition of materials, 3D printing, also known as additive manufacturing, turns geometric representations into tangible items. Because of its quick and geometrically complex capabilities as well as its financial advantages, additive manufacturing (AM), often known as 3D printing, has completely changed the manufacturing industry. Over the past ten years, numerous companies in the automotive, aerospace, medical, and even food industries have implemented this strategy. The most widely used thermoplastic materials in FDM machines are ABS and PLA, making Fused Deposition Modelling (FDM) one of the easiest methods for artists to execute their work. Understanding the characteristics of these materials and the various degradation processes that these polymers may experience as a result of environmental action is crucial from the perspective of art conservation. In this paper it is discussed on 3D printing process, choose materials for 3D printing, such as ABS, PLA, and PET-G, and analyze the printing process based on various criteria. This paper's primary goal is to analyze the dimensional accuracy of 3D printed objects made of various thermoplastic materials using a 3D printer. Though the finished parts have some dimension fluctuation, It is possible to successfully load parts made in 3D design software into printing software.because the accuracy of the printed material improves as the percentage error of the filament material decreases with layer thickness, compared to the design phase specifications